The CSI effect: television, crime and governance - Byers, Michele; Johnson, Val Marie (Critical studies in television, 2009)
CSI as neoliberalism: an introduction / Michele Byers and Val Marie Johnson -- Producing justice, science, and television drama. Science fiction or social fact?: an exploratory content analysis of popular press reports / Liz Harvey and Linda Derksen -- The science and careers of CSI / Sherah VanLaerhoven and Gail Anderson -- CSI and Law & order: dueling representations of science and the law in the criminal justice system / Kurt Hohenstein -- Generic difference and hybridisation in CSI / Nichola Dobson -- Bodies of evidence. The body as abject and object in CSI / Basil Glynn and Jeongmee Kim -- The city of our times: Space, identity and the body in CSI: Miami / Patrick West -- Crime scene investigation as applied environmental history / William Turkel -- Late modern subjects. Not the usual suspects: the obfuscation of political economy and race in CSI / Kevin Bonnycastle -- Troping Mr. Johnson: reading phallic mastery and anxiety on season one of CSI: crime scene investigation / Mythili Rajiva -- Forensic music: channeling the dead on Post-9/11 television / Lawrence Kramer